Technical advancements and pathway integration - Crispin, Mireia; Gallego, Marcos (IE University, 2021)
AI and digital technologies hold promise for a more efficient and effective care delivery. In order to maximise the potential of these emerging technologies and enable their effective integration into European healthcare systems, a concerted, multi-stakeholder effort is necessary, with a particular focus on: Pursuing need-oriented innovation by identifying key areas of systemic need where high-impact innovative solutions can lead to meaningful change for patients and healthcare professionals. Increasing funding of innovative medical technologies by reducing investment risk for private venture capital funds to support highly innovative early-stage ventures. Enabling early real-world testing of post proof-of concept digital products to allow for early user feedback and thus more effective product development. Democratising access to healthcare data by nation-wide and pan-European initiatives aimed at data harmonisation and effective sharing of clinical data. Creating inclusive health technologies by educating future healthcare professionals on tech innovation and entrepreneurship, and by prioritizing and championing the role of patients in technology creation, testing, and implementation.
Keywords: Medtech Innovation; Digital technology; Care delivery; Healthcare system; Healthcare system structures, standards & infrastructure; Data capture; Data exchange; Tecnologías digitales; Cuidados; Sistema sanitario; Estructuras, estándares e infraestructura del sistema de salud; Captura de datos; Intercambio de datos